Hubungan Hipertofi Adenoid Berdasarkan Rasio Adenoid-Nasofaring Dengan Kejadian Otitis Media - Salsabila Salsabila; Prima Maharani Putri; Luhur Dewantoro; Nurrizki Haitamy (Jurnal Sains dan Kesehatan, 2026)
Background: Adenoid hypertrophy is a condition characterized by enlargement of the adenoid tissue which can cause nasopharyngeal obstruction and potentially affect the function of the Eustachian tube. Dysfunction of the Eustachian tube may disrupt middle ear ventilation and increase the risk of otitis media. The degree of adenoid hypertrophy can be objectively assessed using a lateral nasopharyngeal radiograph by calculating the adenoid–nasopharyngeal ratio (A/N ratio). Objective: This study aimed to determine the relationship between adenoid hypertrophy based on the adenoid–nasopharyngeal ratio and the incidence of otitis media. Methods: This study was a quantitative research with an analytic observational design using a cross-sectional approach. Data were obtained from the medical records of patients with adenoid hypertrophy who underwent lateral nasopharyngeal radiographic examination at RSI Purwokerto from 2022 to 2025. The sample consisted of 31 patients who met the inclusion and exclusion criteria. Data analysis was performed using the Spearman correlation test because the data were not normally distributed based on the Shapiro–Wilk test. Results: The results showed that most of the subjects were male (17 subjects, 54.8%) and female (14 subjects, 45.2%). The median age of the subjects was 7 years with an age range of 4–9 years. The median adenoid–nasopharyngeal ratio was 0.90 with a range of 0.68–0.99. Otitis media was found in 11 subjects (35,5%), while 20 subjects (64,5%) did not experience otitis media. The Spearman correlation test showed a correlation coefficient of r = 0.015 with a p-value of 0.936 (p > 0.05), indicating that there was no significant relationship between the adenoid–nasopharyngeal ratio and the incidence of otitis media. Conclusion: There was no statistically significant relationship between adenoid hypertrophy based on the adenoid–nasopharyngeal ratio and the incidence of otitis media.